PROVISION OF EDUCATION TO MOTHERS WITH NUTRITIONAL CHILDREN AT POSYANDU MEKAR JAYA 6 - Cahya Nadila Istiqomah; Sugiatmi . (JURNAL PENGMAS KESTRA (JPK), 2022)
The problem of nutrition in population development is still a problem that is considered a major problem in the world population order. Each country is gradually able to reduce the number of children under five with malnutrition or malnutrition. Malnutrition is the condition of children aged 0-59 months where the body weight according to age is below minus 3 Standard Deviations to less than minus 2 Standard Deviations (-3SD to <-2SD). The program targets are four mothers and toddlers who experience malnutrition problems. The program begins with identifying the problem then formulating the program and implementing the program. Monitoring of Nutritional Status is done by measuring body weight (BB). The method used is re-measurement of nutritional status followed by pre-test and education. In the second week, the post-test was filled by the mother of the toddler and the re-measurement of the nutritional status of the toddler. Community service carried out in the Mekar Jaya Posyandu area 6 RT 03 RW 06 Gondrong Village, Cipondoh District, Tangerang City. Community service was carried out in two meetings within two weeks with mothers of toddlers. Nutrition education related to balanced nutrition was carried out. All programs are conducted door to door in 2 meetings, namely before and after the program. The results of the program are that there is an increase in body weight in four toddlers and an increase in mother's knowledge after being given the intervention. There was an increase in the nutritional status of children under five at the Mekar Jaya 6 Posyandu seen from the z-score value for body weight for age (BB/U) at the beginning and end of the activity.